Economical way to decrease financial burden: anti rabies vaccines by intra dermal administration in developing countries - Kori, Prachi; Toppo, Manju; Patel, Seema (International Journal Of Community Medicine And Public Health, 2020)
Background: To prevent deaths due to rabies only remedy available is post exposure prophylaxis. The major constraint is affordability to anti-rabies vaccine for intramuscular administration or intra dermal administration as PEP. So, intra dermal anti rabies vaccination (IDRV) as recommended by WHO in developing countries like India, reduces the quantity and cost of vaccination, although in most of the health facilities still intra muscular anti rabies vaccination is preferred. Objective of our study is to assess the cost benefit of intra dermal anti rabies vaccination and to find out the demographic profile of patients attending ARV clinic. Methods: It is a hospital record-based study done after ethical committee approval, carried out in a tertiary health care facility, Hamidia hospital, Bhopal (M.P.), India. Results: Our study includes 4818 entries of dog bite cases in whom vaccination cost is found to be approximately Rs. 3,90,420 with Intra dermal administration and it reduces vaccine cost by 60-70% compared with mostly preferred intramuscular vaccination. Among them 31.47% were below 14 years of age and majority 75% were male. Category III bite cases are most common 83.6% and commonest site of dog bite was over the lower limb 68.73%. Conclusions: Intra dermal regimen is more cost beneficial compared to intra muscular regimen, which is thus more helpful to reduce financial burden in developing countries like India.